Sosialisasi AI di SMP Negeri 1 Raja Ampat Untuk Membangun Pemahaman Siswa - Ermin; Dewi Astri Faroeq; Rendra Soekarta; Bita Malissa; Sri Wulandari; La Muhammad Faishal Nurullah; Ilham S; Alfiyyah Faridah (Abdimas: Papua Journal of Community Service, 2025)
The Artificial Intelligence (AI) Socialization Program at SMPN 1 Raja Ampat was implemented as an effort to enhance digital literacy in remote areas. This activity aimed to provide students with a basic understanding of AI concepts and their applications in daily life. The methods used included visual presentations, educational video screenings, simple AI application simulations, and group discussions. Evaluation results showed a significant improvement in students’ understanding of AI, with 90% of participants able to explain basic AI concepts after the program. Moreover, students' interest in learning more about AI technology increased, as reflected by their high enthusiasm and active participation throughout the session. Despite challenges such as limited technological infrastructure and varying levels of student comprehension, the program was successfully adapted to local conditions. This initiative is expected to inspire other schools in remote regions to recognize the importance of digital literacy within their curricula, thereby promoting equitable access to knowledge and preparing students for future technological advancements.